The Paradigm of Islamic Education Management in the Era of Globalization - Sevia Umi Wardini (CV. Agrapana Media, 2026)
Globalization has brought significant changes to the management of educational institutions, including Islamic education, which is required to be adaptive, professional, and competitive without losing its Islamic identity. The main issue addressed in this study is the persistent gap between the ideal values of Islamic education management and management practices that are capable of responding to global challenges. This study aims to analyze the paradigm of Islamic education management in the era of globalization and its implications for educational quality. The research employs a library research method by examining various literature sources, including textbooks, academic journals, and scholarly works relevant to Islamic education management and globalization. Data are analyzed using content analysis techniques to identify emerging concepts, patterns, and management paradigms. The findings indicate that the paradigm of Islamic education management has shifted toward an adaptive and integrative model that combines Islamic values with modern management principles. Islamic education management is no longer merely administrative in nature but is oriented toward quality improvement, professionalism, and human resource development. Globalization does not weaken Islamic values; rather, it encourages their actualization within management practices. The implications of this study highlight the urgent need for Islamic educational institutions to implement value-based governance systems that integrate strategic management, quality assurance, and professional human resource development rooted in Islamic principles. This paradigm shift positions Islamic values not merely as normative foundations but as operational frameworks that enhance institutional competitiveness, sustainability, and holistic educational excellence in the era of globalization.